Bio-theraprutic intervention for dengue infection-present scernario on plant-based remedies: A review article - Lavanya, D.; Parthasarathy, K.; Soytong, K.; Sounderrajan, V.; Manickam, R. (My University, 2024)
Dengue virus (DENV), a member of the Flaviviridae, is the causative organism of Dengue hemorrhagic fever and Dengue Shock Syndrome. It exists as 4 serotypes (DEN1-4), all of which can cause full spectrum of the disease. Dengue is one of the most re-emerging arboviral diseases in the world with a record of 390 million cases globally, putting 3.9 billion people at the risk of infection annually. With dengue being enlisted as a high burden disease in the tropical countries, there is a dire need to bring about efficient therapeutics that help to prevent and treat the diseased population. The present mode of treatment of Dengue is based on the management of symptoms and includes the use of Non-steroidal Anti-inflammatory Drugs (NSAIDs), antibiotics, antipyretics and corticosteroids. These provide symptomatic treatment and also bring about undesirable side effects. Presently, there are no approved vaccines or antivirals for Dengue treatment in India. It is thus important to consider the biology of the virus with special focus on identification of effective anti-viral targets for therapy. With the alleviation of symptoms alone being insufficient for the disease treatment, there is a shift in research to find alternative forms of medicine for the treatment of the disease. Herbal remedies have a long history of use in ancient medical systems and are now widely accepted as safe, natural substitutes for pharmaceutical treatments. But in order to guarantee consistency and safety, the growing demand for these items calls for strict quality control methods. In particular, leaves of Carica papaya and Nilavembu kudineer are potential candidates for this purpose. This review focuses on bringing to light the various therapeutic interventions presently in use and emphasize the significance of quality control techniques in regulating various aspects of the development, manufacturing, and distribution of herbal products.
Keywords: Carica papaya; Flaviviridae; Herbal technology; Nilavembu Kudineer; NSAIDs